(untitled) (Annals of Medical Research, 2021)
Environmental noise which is a negative effect on workman health and work security is a social problem ofour country that is on the process of industrial development. This problem cause sensorineural permanent hearing loss that is a result of negative effects on industrial workman, especially. In this study, hearing thresholds of 101 workers who work in a various noisy environmental in a sugar factory of our country were determined audiometricallyand negative effects ofnoisy environmental on the workman health. Statistically, significant differences were found with respect to hearing loss between workers exposed to noise levels under 80 dB and above 87 dB (p0.05) and between workers exposed to noise under and above 5 years (p0.001). These results show that hearing protection measures, such as education, protective cask and modernize of noisy factory, are absolutely needed for workers who work in a noisy environmental.